Predictive ability of self-efficacy in emotional expression among a sample of university students in the province of Sweida. (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The aim of the current research is to know the relationship between self-efficacy and emotional expression among a sample of university students, to reveal the predictive ability of each of the dimensions of the self-efficacy scale in emotional expression among the members of the research sample, and to reveal the differences in the level of  self-efficacy and the level of emotional expression among the sample  members according to the gender variable, Where the research sample consisted of (300) male and female students from the university students within the province of Sweida, and the Self-Efficiency Scale prepared by Morris (2002), and the Berkeley Emotional Expression Scale, prepared by Gross & John & Richards (2000), were applied.  The results showed the existence of a statistically significant correlation between self-efficacy and emotional expression, and the existence of a statistically significant relative contribution to each of the dimensions of self-efficacy (social, academic, and emotional self-efficacy) to predict emotional expression, it also showed existence of a joint contribution (20%) for dimensions of self-efficacy in predicting emotional expression, and the highest percentage was for the social self-efficacy dimension. in addition to the absence of statistically significant differences in the level of self-efficacy according to the gender variable, while there are statistically significant differences in the level of emotional expression according to the gender variable in favor of females.